Clinical Evaluation of the Time-effect Relationship of Auriculoacupuncture at Point Zero on Autonomic Function among Healthy Volunteers: An Exploratory Three-arm Study - Annamalai Dharuman; Deepa Saravanan; Prabu Narasimman; Geethanjali Sankar; Narmatha Murugan; Madhumitha Vellingiri; Abirami Balu (Journal of Acupuncture Research)
Background: Auriculoacupuncture (AA) has been used in traditional Chinese medicine for over 2,500 years to restore qi and blood balance. Point Zero is a key AA point known for its autonomic modulation effects. However, the optimal needle retention duration has not yet been established. Studies have suggested that AA influences heart rate variability (HRV) and pain modulation at different retention times. The aim of this study to investigate the influence of needle retention duration at Point Zero on HRV and peak expiratory flow rate (PEFR). This study hypothesized that a longer needle retention duration enhances autonomic modulation, thereby aiding clinical standardization. Methods: This exploratory three-arm study included 90 healthy volunteers from the International Institute of Yoga and Naturopathy Medical Sciences, who were assigned to three groups (arms), each with 30 participants. All study participants will undergo AA at Point Zero on both sides of the ear, and the needles will be retained (Arm 1 for 5 minutes, Arm 2 for 30 minutes, and Arm 3 for 60 minutes). The primary outcome will be the assessment of cardio-autonomic modulation via HRV analysis, while the secondary outcome will be the measurement of PEFR before and after the intervention. Results: This study hypothesized that the needle retention duration at Point Zero is expected to have a major impact on autonomic function, as indicated by the HRV and PEFR values. Conclusion: This study will discuss the significance of needle retention duration and its impact on autonomic function and respiratory outcomes.